2013
DOI: 10.1002/lpor.201300068
|View full text |Cite
|
Sign up to set email alerts
|

4H‐SiC: a new nonlinear material for midinfrared lasers

Abstract: Nonlinear optical (NLO) frequency conversion is commonly used for generating midinfrared (MIR) lasers that offer light sources for a variety of applications. However, the low laser damage thresholds of NLO crystals used so far seriously limit the output power of MIR lasers. Here, a new nonlinear material 4H-SiC is demonstrated for producing MIR laser. Broadband MIR radiation ranging from 3.90 to 5.60 μm is generated in 4H-SiC by phase-matched difference-frequency generation for the first time.The results may o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 36 publications
(42 reference statements)
7
55
0
Order By: Relevance
“…So far, this outstanding material has received little attention in experimental works that are limited to the demonstration of nonlinear properties in the near infrared [17], mid-infrared DFG above the optical phonon frequencies [18], and emission of 1 THz radiation from 6H-SiC [19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, this outstanding material has received little attention in experimental works that are limited to the demonstration of nonlinear properties in the near infrared [17], mid-infrared DFG above the optical phonon frequencies [18], and emission of 1 THz radiation from 6H-SiC [19].…”
mentioning
confidence: 99%
“…Recently, preliminary investigations by Naftaly et al [16] suggested 4H-SiC as a crystal suitable for nonlinear optics in the multi-terahertz range. So far, this outstanding material has received little attention in experimental works that are limited to the demonstration of nonlinear properties in the near infrared [17], mid-infrared DFG above the optical phonon frequencies [18], and emission of 1 THz radiation from 6H-SiC [19].…”
mentioning
confidence: 99%
“…Images reproduced from [23,24,29] with Copyright permission 2014-2015, AIP Publishing LLC characterised by three independent components of the second-order nonlinear optical tensor, recently measured accurately as d 31 = d 32 = 6.7(6.5)pm/V, d 15 = d 24 = 6.5(6.7)pm/V and d 33 = −12.5(−11.7)pm/V in 6H (4H). The refractive indices and the birefringence are used to determine if phase matching can be realised; they have been remeasured from the visible to the mid-infrared region, and Sellmeier equations for ordinary and extraordinary refractive index in 4H and 6H have been provided [76]. This has led to mid-infrared region laser output tunable from 3.90 to 5.60 µm by phase-matched difference frequency generation in 4H-SiC.…”
Section: Nonlinear Effectsmentioning
confidence: 99%
“…1(d)] is obtained and it exhibits high transmittance below 4 μm. In fact, as one of our previous works, femtosecond MIR pulses generated by difference frequency generation (DFG) process using 4H-SiC has been reported [29].…”
mentioning
confidence: 97%
“…First, it possesses orders of magnitude higher damage threshold (80 GW∕cm 2 ) [28] than traditional MIR nonlinear crystals partly because of its strong C-Si covalent bond. Second, based on the Sellmeier equations of 4H-SiC crystal [29], type II phase matching condition can be satisfied [ Fig. 1(a)].…”
mentioning
confidence: 99%